O-028 The intrasaccular seal© device: improved flexibility and healing. (4th August 2020) - Kraitem, A; Gounis, M; Vardar, Z; King, R; Langan, E; Wolfe, T; Badruddin, A; Periera, E; Follmer, B; Rosqueta, A; Zaidat, O
Abstract : Background: The new generation of intrasaccular flow disruptors offers several potential advantages in aneurysm treatment. 1 2 However, questions regarding risks for thromboembolic complications 3 4 and long-term treatment durability remain. We study the safety and effectiveness of three Galaxy Therapeutics Seal© intrasaccular prototypes: A, B, and C (Galaxy Therapeutics LLC, Brookfield, WI). Methods: Aneurysms were created in thirteen rabbits and one of 3 Seal devices were implanted. High frequency optical coherence tomography (HF-OCT) and Digital Subtraction Angiography (DSA) was performed 4- and 12-weeks post-implant. After 12 weeks, the parent vessel and the aneurysm were explanted for histological analysis. One rabbit developed symptoms consistent with a lumbar spine injury and was euthanized and explanted at day 56. Results: 12-week DSA and OCT images demonstrated 8 animals had a satisfactory aneurysm occlusion (group 1: complete blood flow disruption or contrast filling in marker recess) and 4 into group 2 (residual neck or aneurysm). The percentage of neointimal coverage of the device at four-weeks was greater for group 1 ( 78 ±22.6 %) than for group 2 ( 37 ±4.7 % ) ( p= 0.006 ) which persisted at 12-weeks (87.5± 14 % vs. 41± 3.1 % respectively; p= 0.004 ). There was no statistical difference between groups 1 and 2 in either baseline neck gap areas ( 0.8± 0.64 mm 2 vs. 2.6± 1.42 mm 2, respectively; p= 0.808 ) nor in baseline neck gap volumes ( 26± 26 mm 3 vs. 113.11± 134.17 mm 3, respectively; p= 0.361 ). Representative examples of pathology are shown in the figure 1 . Conclusion: Preliminary evidence in this preclinical study highlight advantages of a new generation of intrasaccular aneurysm embolization technology in terms of flexibility and optimization of healing features, particularly in the A and C cohorts. References: Radiology 2014;273:194–201. J Neurointerv Surg 2019;11:1150–1154. World Neurosurg 2018;109:e183–e193. J Neurointerv Surg 2018;10:553–559. Disclosures: A. Kraitem: None. M. Gounis: 1; C; Research grant to institution to fund experiments by Galaxy Therapeutics. Z. Vardar: None. R. King: None. E. Langan: None. T. Wolfe: 4; C; Founder, Galaxy Therapeutics. A. Badruddin: 4; C; Founder, Galaxy Therapeutics. E. Periera: 4; C; Founder, Galaxy Therapeutics. B. Follmer: 5; C; Galaxy Therapeutics. A. Rosqueta: 5; C; Galaxy Therapeutics. O. Zaidat: 4; C; Founder, Galaxy Therapeutics.